Long-term blood pressure behavior and progression to end-stage renal disease in patients with immunoglobulin A nephropathy: a single-center observational study in Italy. Issue 5 (May 2020) - Russo, Elisa; Verzola, Daniela; Salvidio, Gennaro; Bonino, Barbara; Picciotto, Daniela; Drovandi, Stefania; Pozzi, Claudio; Ferrario, Francesca; Pontremoli, Roberto; Garibotto, Giacomo; Viazzi, Francesca
Abstract : Background: Antihypertensive treatment by the use of RAAS inhibitors (RAAS-is) is of paramount importance in the management of slowly progressive IgA nephropathy (IgAN). With the aim of better understanding the relationship between BP behavior and progression, we looked at time-averaged SBP and time-averaged proteinuria and renal outcome in a single-center cohort of IgAN patients. Methods: Among 248 consecutive patients referred to the Clinic of Nephrology of San Martino Hospital from 1996 to 2018 for native renal biopsy with a diagnosis of IgAN, we retrospectively analyzed 145 with available data at baseline and during follow-up. All patients received Supportive Care, 39% were on RAAS-is alone, 45% plus steroids, and 16% plus steroids and immunosuppressors. Renal replacing treatment (RRT) was the primary endpoint. Results: During a mean follow-up of 67 ± 6 months, 23% of study patients ( n = 33) progressed to RRT and 6% ( n = 9) died. Patients who reached the renal endpoint, had lower baseline eGFR and higher proteinuria and proteinuria indexed at baseline. Moreover, they had higher TA-SBP (139 ± 17 vs. 130 ± 13, P = 0.0016). The incidence of RRT was higher in IgAN patients in the highest time-averaged SBP tertile as compared with the others (32 vs. 23 vs. 9%, χ 2 6.8, P = 0.033). After adjusting for baseline SBP, baseline and time-averaged proteinuria indexed, MEST-C score, and treatment, the association between TA-SBP and RRT persisted. Conclusion: Time-averaged low BP values were independently associated to a decreased risk of renal progression in IgAN with no evidence of a J-curve relationship even at SBP levels below 125 mmHg. Abstract : Supplemental Digital Content is available in the text